(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2017)
Cooking is the vital process of rendering potential foodstuffs edible, accessible and appropriate both in biological and in socio-cultural terms. Despite being too long neglected in archaeological studies, the food production processes have left remains that make up a very large part of the archaeological record. The aim of this paper is to outline a scenario of the Greek-style cooking vessels found along the western Mediterranean coasts between the Archaic and the Hellenistic period, namely within the main Etruscan and Greek ports of trade and wrecks, in order to highlight the cultural impact and the developments of this crucial aspect in the cultural and social life. The main objects of the research is a particular cooking ware produced in Greece between the sixth century BCE and the Romanization, widespread all around the Mediterranean sea, consisting of handy and refractory vessels (named for example chytra, kakkabe, lopas, thyeia etc.). The case-study is the Adriatic hub of Spina (near Comacchio, Ferrara), founded by the Etruscans at the end of the 6th century BCE, and one of the main economic partners of Athens during the 5th until the middle 4th BCE. Ongoing multidisciplinary projects are trying to return the complex interaction between the local (i.e ‘etruscan’) culinary habits and the Greek culture, in terms of availability, preferences, economic choices, trough the adoption of multiple investigation methodologies including archaeology, archaeometry, archaeozoology, archaeobotany, biochemistry.